PREVALENSI DAN KARAKTERISTIK NYERI KEPALA TERKAIT EPILEPSI DI RS HASAN SADIKIN BANDUNG - Mariana, Henny Anggraini Sadeli, Suryani Gunadharma (Neurona Majalah Kedokteran Neuro Sains, 2014)
INTRODUCTION EPILEPSY AND HEADACHE ARE THE MOST DISABLING DISORDERS IN COMMUNITY SEIZURERELATED HEADACHE CAN BE DIVIDED INTO PREICTAL ICTAL AND POSTICTAL HEADACHE HEADACHE CAN BE USED AS A GOOD PREDICTION ANDOR INDICATOR OF THE SEIZURE